Pengaruh Optimisme Dan Kemampuan Penyelesaian Masalah Terhadap Kesejahteraan Psikologi Pada Mahasiswa - Anggi Saputra Nasution; Ahmad Fauzan Al Ghifari; Muhamad Afif Abdilah; Lucky Purwantini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In higher education settings, undergraduates also face complex dynamics that include academic pressures, social changes, and personal development demands which can negatively impact aspects of psychological well-being in students. Various elements can affect a person's psychological well-being, including culture, age, gender, and the way a person interprets experiences in their life. This study aims to determine the effect of optimism and problem-solving skills on psychological well-being in college students. This research is correlational quantitative research. The subjects in this study amounted to 135 students. The sampling technique used is random sampling. The results showed that the F value was 152.525 with a significant value of p = 0.000 where (p <0.05) which means that there is a significant effect of optimism and problem-solving ability on psychological well-being, so Ha is accepted and the R2 coefficient value (R Square) of 0.835 or (84%) which this value shows the influence of optimism and problem-solving ability on psychological well-being by 84% while the remaining 16% is influenced by other variables not examined. This study concludes that optimism and problem-solving ability affect psychological well-being positively and significantly, which means that the more optimism and problem-solving ability increase, the more psychological well-being levels will increase